The influence of strategic competitive response capability on the performance of commercial organizations in Kenya listed in Nairobi securities exchange - Peter Ngugi (Technium Social Sciences Journal, 2024)
Strategic competitive response has been identified as effective factor that harnesses a business ability to utilize all its skills, capabilities and resources in order to gain competitive advantage and thus survive and increase its value over time. It focuses on the organization’s assets, resources and market position, projecting how well it will be able to employ strategies in the future. This study sought to explore the influence of strategic competitive response capability deployment on performance of listed organizations in Nairobi securities exchange. There is a dearth of studies empirically investigating the relationship between interaction of strategic competitive response capability deployment and organizational performance. This gap in knowledge is exacerbated by multiple definitions, ambiguity of constructs, contradicting views and little grounding of the theory in empirical observation. The objective was to determine the influence of strategic response capability performance. The study employed two theories to explain the interaction of strategic competitive response action and organizational performance, the theories were resource-based view and dynamic capabilities theory. A cross sectional research design was employed with the focus set on the operations of corporations listed in Nairobi securities exchange. A census survey of 67 firms was conducted. The results show that strategic competitive response has a positive statistically significant relationship with performance (β=0.600, p=.000). The results have also shown that strategic competitive response was positively correlated to organizational performance at 99% confidence level (r=6.45, p=0.000).This study concludes that strategic competitive response capability significantly influences organizational performance positively. The findings of this study would help firms listed in the Nairobi Securities Exchange identify critical factors and design sustainable strategies to improve their strategic competitive response capability through strategic planning and ensuring that they are up to date with modern trends in technology and other information related to their industry.